EVIDENCE OF HERZBERG'S MOTIVATION-HYGIENE THEORY IN SMALL AND MEDIUM ENTERPRISES THROUGH THE LENS OF A THREE-STAR HOTEL - AhomkaYeboah, Moses; Abdulai, Alhaji (International Journal of Research -GRANTHAALAYAH, 2016)
This paper utilized Herzberg's motivation-hygiene theory to determine the extent to which employees of Coconut Grove Hotel feel motivated and what motivational offers influence their high performance? A census approach was employed and questionnaire used to collect data from 80 employees. The data was analysed with descriptive statistics. The results show that employees experience high levels motivators and hygiene factors in their respective departments and monetary compensation had the most significant influence in spurring them to higher performance. To further boost employees’ motivation, the management of Coconut grove hotel must entrenched a culture of fair treatment, respect and recognition coupled with "different strokes for different folks" approach by having regular one–on-one conversations with employees to find out what matters to them. Employees must be given greater responsibility for planning, managing and controlling their work, and also be rewarded with money for excellent job performance. Employees must be assisted to grow within their jobs and accessible opportunities for their career development.